2021
DOI: 10.1093/humrep/deab146
|View full text |Cite
|
Sign up to set email alerts
|

Positioning the donor in a new landscape—mothers’ and fathers’ experiences as their adult children obtained information about the identity-release sperm donor

Abstract: STUDY QUESTION How do heterosexual parents experience identity-release donation when adult children have obtained information about their sperm donor? SUMMARY ANSWER Adult offspring’s receipt of identifying information about the sperm donor challenged the fathers’ role as a parent, which was reflected in how parents positioned the donor in relation to the family. WHAT IS KNOWN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Parents should understand that the disclosure of birth via DC to the offspring at an early age might contribute to a better development of their offspring’s identity; survey responses indicated that parents who understand this started such disclosures sooner [ 36 ]. Another study revealed that some parents of offspring conceived with donor sperm consider the donor as separate from the family; however, the rearing fathers’ role as a parent can be challenged when the adult offspring receive identifying information about the sperm donor [ 37 ]. In addition to the aforementioned practical difficulties in handling donor anonymity, these ethical issues surrounding the identity of donor-conceived offspring suggest that a shift to non-anonymous DC should be socially useful and that the existing non-anonymous DC system also needs to be reconsidered in order to help parents disclose DC to offspring.…”
Section: Resultsmentioning
confidence: 99%
“…Parents should understand that the disclosure of birth via DC to the offspring at an early age might contribute to a better development of their offspring’s identity; survey responses indicated that parents who understand this started such disclosures sooner [ 36 ]. Another study revealed that some parents of offspring conceived with donor sperm consider the donor as separate from the family; however, the rearing fathers’ role as a parent can be challenged when the adult offspring receive identifying information about the sperm donor [ 37 ]. In addition to the aforementioned practical difficulties in handling donor anonymity, these ethical issues surrounding the identity of donor-conceived offspring suggest that a shift to non-anonymous DC should be socially useful and that the existing non-anonymous DC system also needs to be reconsidered in order to help parents disclose DC to offspring.…”
Section: Resultsmentioning
confidence: 99%
“…The large majority of participants were living with the co-parent of the donor-conceived child. Participants' demographics have previously been reported (Lampic et al, 2021) and are presented in TABLE 1. Responders and non-responders at the fourth wave were compared with regard to disclosure intentions and behaviour assessment when the children were 1-4 years of age (Isaksson et al, 2012), and no significant group differences were found (data not shown).…”
Section: Participantsmentioning
confidence: 99%
“…Heterosexual couples have been shown to be less likely to disclose their use of sperm donation to their children (Beeson et al, 2011;Freeman et al, 2016) and to express concerns about the impact of disclosure (Blake et al, 2010;Readings et al, 2011;Widbom et al, 2021). In comparison, single women and same-sex female couples tend to be open with their children about their conception with donor spermatozoa as they need to explain the absence of a father in the family (Appleby et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a third told only their mother and free-text comments suggest that this decision may have been related to worry that it might upset the father. Indeed, findings from a recent interview study with sperm donation parents indicate that adult offspring’s interest in the donor’s identity could challenge the father’s position, and trigger emotions related to his infertility ( Widbom et al , 2021 ). Further studies are needed to explore parents’ as well as identity-release donors’ experiences of contact between the donor and offspring from their donation.…”
Section: Discussionmentioning
confidence: 99%